The Chronicler in Stone - Gayathri M.V, Gayathri M.V (International Journal of Psychosocial Rehabilitation, 2011)
This article analyses the Albanian writer Ismail Kadare’s attitude to Communist regime through his early written novel, Chronicle in Stone. It documents the formation of the writer’s consciousness in the era preceding the communist Gleichschaltung. In counterpoint to the encomiums paid to Hoxha’s Stalinist purism and Albanian patriotism at the high point of the regime, Kadare reminds his fellow countrymen of the origins of Albanian communism in civil war, terror, revenge, and summary justice. Moreover, it is the subjective authenticity of the narrative voice, not the objective authenticity of socialist realism, which gives meaning to Kadare’s struggles against dictatorship.